The impact of physical disability on activities of daily living of physically disabled persons attending tertiary care centre of Nagpur using Barthel’s scale: a cross-sectional study - Raut, Roshan U.; Thakre, Sushama S.; Thakre, Subhash B. (International Journal Of Community Medicine And Public Health, 2020)
Background: Disability reflects the difficulties that the disabled person experiences during physical movement as well as interaction with the society. This restrictions act as barrier for executing daily living activities which results into poor health outcome and increased dependency. The objective is to study impact of physical disability on activities of daily living (ADL) of physically disabled person. Methods: A present cross-sectional study was undertaken at Indira Gandhi government medical college, Nagpur. Physically disabled persons aged more than 18 years of age attending outpatient department for disability were included in this study. This study was carried out from 1st May to 31st September 2018. In all total 83 subjects were enrolled in this study. For assessment of activity of daily living Barthel index was used. Descriptive statistics (frequencies and percentage) were obtained and data was analysed by using Microsoft Excel and Epi-Info version 7.2. Results: In all 83 rural subjects were considered for final analysis. Out of 83 subjects 49 (59.04%) were male and 34 (40.96%) were female. Mean±SD age in years was 40.5±12.9. Majority of study participants were belonging to class IV and V category of socio-economic status. Activities such as transfer, mobility, and stair climbing showed greater impact of physical disability. It was found that 18.1% respondents required major help for transfer as an ADL. Conclusions: It is clear from the present study that the activity of daily living is impacted due to disability. In every activity domain it was found that majority were independent.